Cluster Analysis of Online Shop Product Reviews Using K-Means Clustering - Rena Nainggolan; Eviyanty Purba (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose:This research aims to mine review data on one of the e-commerce sites which ultimately produces clusters using the K-Means Clustering algorithm that can help potential customers to make a decision before deciding to buy a product or service. Design/methodology/approach: By using Octoparse we mine opinion or comment data in the form of customer online reviews, after getting the data we group the data using the k-emans clustering methode to obtain cluster Findings: Cluster Analysys can can help potential customers to make a decision before deciding to buy a product or service Research limitations/implications: WWW.Lazada.Com Practical implications: State your implication here. Originality/value: Paper type: This paper can be categorized as case study paper